Spirituality and Posttraumatic Growth in Adolescent Girls with Dating Violence Experience - Aqila Kerinina; Chandradewi Kusristanti (Islamic Psychology Department, Dakwah Faculty of Universitas Islam Tribakti Lirboyo Kediri, 2023)
There are many cases of violence among adolescent girls who have experienced violence in dating in Indonesia. Even though dating violence is painful, adolescent girls can grow in a way called posttraumatic growth after the event. Spirituality can help people find meaning and purpose in their lives, which may help them recover from trauma. This study aims to determine the significance of the role of spirituality on posttraumatic growth in adolescent girls who have experienced dating violence. This study uses a quantitative approach with DSES to measure spirituality (α=0.932) and PTGI-SF to measure posttraumatic growth (α=0.812). Participants in this study were adolescent girls (15-25 years old) with dating violence experience (N = 309). The result shows that spirituality was crucial for posttraumatic development (R² = 0.156, p =.000). The results of this study can be helpful as a reference for conducting interventions targeted at adolescent girls to increase their spirituality and knowledge of healthy relationships.